(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Lipoid proteinosis is a rare genodermatosis with autosomal recessive inheritance. It is a multisystem disorder characterized by progressive deposition of hyaline material in the skin, mucous membrane and different organs of the body. The disease is presented by dermatological, laryngeal, ophthalmological, and neurological manifestations. Involvement of oral mucosa may lead to xerostomia and dysphagia; involvement of larynx and eyes results in hoarseness of voice at early infancy and moniliform blepharosis. Extracutaneous involvement includes neurological manifestations like psychosis, partial complex seizures, anger, panic attacks, and progressive amnesia. Till date around 300 cases have been reported in literature. Case Report: A 63 years old male patient reported with chief complaints of pain in the right and left cheek region, difficulty in swallowing food and dryness of mouth. Conclusion: Lipoid Proteinosis requires multidisciplinary opinion and evaluation by dermatologists, ophthalmologists, otolaryngologists, neurologists and psychiatrist. Clinical features and histopathological evaluation aids in the confirmation of the disease. Lipoid proteinosis should be considered one among the differential diagnosis when patient reports with difficulty in mouth opening, enlarged tongue, difficult in chewing and swallowing.